A First Approximation of the Global Energy Consumption of Ball Bearings. Issue 5 (3rd September 2021) - Bakolas, Vasilios; Roedel, Philipp; Koch, Oliver; Pausch, Michael
Abstract: Rolling element bearings are found in every piece of machinery and are therefore a source of energy losses that cannot be ignored. In recent years a series of energy-efficient bearings have been developed using specific designs or new materials aiming to reduce the losses of a bearing without sacrificing its load-carrying capacity. The effect that these designs have on the global energy consumption has not been quantified until now. A methodology to estimate the energy losses of the usage of a specific bearing type on a global scale is presented in this article. The method, which is based on current standards, provides a first approximation for the determination of the energy losses of bearings and is tested for its plausibility. The pros and cons of the proposed method are discussed, and a proposal is made regarding how to calculate the potential energy efficiency of newer designs.